Transparent copolymer resin, preparation method thereof and resin composition containing transparent copolymer resin
By preparing the styrene-acrylonitrile-acrylate terpolymer transparent resin with low refractive index temperature dependence, the problem of the optical performance of existing transparent ABS resins deteriorated when temperature changes are changed, and more stable high transparency and Good liquidity.
Patent Information
- Application Number
- CN202411789968.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The optical performance of existing transparent ABS resins decreases when temperature changes, causing the product to fog and affect its application effect.
A preparation method is used to prepare a styrene-acrylonitrile-acrylate terpolymer transparent resin. The resin has a low refractive index temperature dependence within a temperature of 10-60°C. By controlling the reaction conditions and the monomer ratio, Ensure that the refractive index of the resin is within the range of 1.520-1.510.
The fluidity and transparency of the transparent resin are improved, and the defect of its optical performance deterioration when temperature changes are reduced, which significantly improves the application performance of transparent ABS resin.
Smart Images

Figure CN119431649A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a transparent copolymer resin, a preparation method thereof and a resin composition containing the transparent copolymer resin, and belongs to the field of polymer materials. Background Art
[0002] Styrene-acrylonitrile-acrylate terpolymer is a transparent resin that can be used alone as a plastic, but is mainly mixed with acrylonitrile-butadiene-styrene (ABS) graft rubber to prepare transparent ABS.
[0003] Transparent ABS resin is often used in washing machine covers, windows and other parts. It can be prepared by blending and extruding grafted rubber (rubber powder phase) and matrix resin (resin phase). Whether the refractive index of the two phases is consistent determines whether the transparent ABS has good optical properties.
[0004] Chinese patent publication number CN1372579A discloses a styrene-acrylonitrile-methyl methacrylate terpolymer prepared by bulk polymerization. By controlling the ratio of monomers, the refractive index of the resin is adjusted within the range of 1.513-1.521 to obtain a transparent ABS resin composition.
[0005] Chinese patent publication number CN101072803A discloses a resin composition having good transparency, drug resistance and anti-fading properties prepared by bulk polymerization of styrene monomer, methyl methacrylate monomer, acrylonitrile monomer and an antioxidant.
[0006] The transparent ABS resin prepared by blending the copolymer of styrene monomer, methyl methacrylate monomer and acrylonitrile monomer disclosed in the above patent documents with acrylonitrile-butadiene-styrene (ABS) grafted rubber is mainly used to improve transparency, and introduce antioxidants to alleviate the presence of acrylonitrile and styrene with poor heat resistance, thereby optimizing the color of the resin. However, the introduction of antioxidants causes a certain degree of loss in the transparency of the resin.
[0007] It is known that most of the transparent ABS resins on the market are prepared by blending the rubber powder phase and the resin phase. The key technology is to control the refractive index of the two phases to be consistent, so that the ABS resin can be transparent at a certain temperature. It is well known that the refractive index of polymers has a certain temperature dependence and decreases with increasing temperature. Since the refractive index of the two phases has different corresponding relationships within a certain temperature range, the optical performance of transparent ABS will decrease under different temperature conditions, causing the product to fog, such as the water temperature heating function of the washing machine, which may affect the window observation effect.
[0008] The temperature dependence of the refractive index is essentially related to the mobility of the polymer molecular chain. The more flexible the molecular chain, that is, the lower the glass transition temperature, the smaller the effect of temperature on its refractive index, and vice versa. In other words, for the transparent ABS prepared by blending, since the molecular chain of the rubber powder phase is more flexible and the molecular chain of the resin phase is more rigid, when the temperature changes, the change trend of its refractive index is inconsistent, which will cause the transparent ABS to gradually fog up as the temperature changes, resulting in poor optical properties.
[0009] Therefore, it is very necessary to develop a styrene-acrylonitrile-acrylate resin with high transparency, good fluidity and low temperature dependence of the refractive index. Summary of the invention
[0010] In order to solve the above technical problems, the present invention provides a method for preparing a transparent copolymer resin, and more specifically, the present invention relates to a method for preparing a styrene-acrylonitrile-acrylate terpolymer transparent resin and a resin composition comprising the styrene-acrylonitrile-acrylate terpolymer transparent resin. The transparent resin has low odor, low processing temperature, good hue and high transparency due to good fluidity; and the temperature dependence of the refractive index of the transparent resin phase is low, thereby reducing the defect that the optical properties of the transparent ABS resin deteriorate with temperature changes.
[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0012] A styrene-acrylonitrile-acrylate terpolymer transparent resin, wherein the refractive index of the terpolymer transparent resin has a low temperature dependence within a temperature range of 10 to 60°C, and the relationship between the refractive index y and the temperature x (°C) satisfies a linear relationship: y=a1x+b1, and a1 is between -0.03% and -0.01%, b1 is between 1.5 and 1.6, and the terpolymer transparent resin has a refractive index of 1.520-1.510.
[0013] The present invention also provides a method for preparing the above styrene-acrylonitrile-acrylate terpolymer transparent resin.
[0014] A method for preparing a transparent copolymer resin, the method comprising the following steps:
[0015] a) mixing an aromatic vinyl monomer, an alkyl (meth)acrylate monomer, an unsaturated nitrile monomer, an organic peroxide initiator A, a chain transfer agent and a reaction medium to obtain a reaction mixture;
[0016] b) adding the reaction mixture described in a) to the reactor 1) to carry out bulk polymerization reaction, the reaction temperature is 130-145° C., the reaction temperature of the reactor 1) is regulated by gas phase circulating liquid, wherein the temperature of the gas phase circulating liquid is 30-40° C., and the proportion of the reaction medium in the circulating liquid is 15-25%. The bulk polymerization conversion rate is controlled to be 50-55%, and a polymerization mixture is obtained.
[0017] c) adding the polymerization mixture described in b) and organic peroxide initiator B to reactor 2) to carry out bulk polymerization reaction, the reaction temperature is 145-155° C., the temperature of gas phase circulating liquid in reactor 2) is 20-30° C., the proportion of reaction medium in the circulating liquid is 35-45%. The bulk polymerization conversion rate is controlled to be 75-80%, and a polymerization mixture is obtained.
[0018] d) After step c), the polymerization mixture is transferred to a devolatilizer to remove light components to obtain a transparent copolymer resin.
[0019] In the preparation method of the present invention, preferably, the amounts of the components in step a) are: 50 to 70 parts by weight of an alkyl (meth)acrylate monomer, 10 to 30 parts by weight of an aromatic vinyl monomer, 5 to 20 parts by weight of an unsaturated nitrile monomer and 10 to 20 parts by weight of a reaction medium.
[0020] Preferably, in step a), based on 100 parts by weight of the aromatic vinyl monomer, (meth) alkyl acrylate monomer, unsaturated nitrile monomer and reaction medium mixture described in a) (referred to as "initial raw material and reaction medium mixture"), the amount of organic peroxide initiator A added is 0.01 to 0.03 parts by weight, and the amount of chain transfer agent added is 0.05 to 0.2 parts by weight.
[0021] In the preparation method of the present invention, preferably, in step c), the amount of the organic peroxide initiator B added is 0.002 to 0.005 parts by weight based on 100 parts by weight of the mixture of the initial raw materials and the reaction medium.
[0022] In the preparation method of the present invention, preferably, in step d), the devolatilization temperature is 210-240° C., the absolute pressure is 3-10 kPaa, and the devolatilization time is 10-15 min.
[0023] Preferably, the (meth)acrylic acid alkyl ester monomer used to prepare the transparent copolymer resin of the present invention includes one or more of methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, and butyl acrylate. More preferably, the (meth)acrylic acid alkyl ester is methyl methacrylate.
[0024] Preferably, the aromatic vinyl monomer used to prepare the transparent copolymer resin of the present invention includes at least one of styrene and α-methylstyrene. More preferably, the aromatic vinyl monomer is styrene.
[0025] Preferably, the unsaturated nitrile monomer used to prepare the transparent copolymer resin of the present invention includes at least one of acrylonitrile and methacrylonitrile. More preferably, the unsaturated nitrile monomer is acrylonitrile.
[0026] Preferably, the reaction medium used in the present invention is one or more of cyclohexane, toluene, xylene, ethylbenzene, preferably toluene.
[0027] Preferably, the organic peroxide initiator A used in the present invention is at least one of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane and 1,1-bis(tert-butylperoxy)cyclohexane; the organic peroxide initiator B is one or more of cumene peroxide and dicumyl peroxide, more preferably dicumyl peroxide.
[0028] Preferably, the chain transfer agent used in the present invention is a mercaptan-based compound including at least one of tert-dodecyl mercaptan and n-octyl mercaptan, and more preferably, the chain transfer agent is n-octyl mercaptan.
[0029] The transparent copolymer resin prepared by the method of the present invention has a glass transition temperature of 80 to 95° C., a molecular weight distribution of 2.0 to 2.3, a monomer residue of 1000 ppm or less, a melt index of 30 or more, a b color value of 1 or less, a refractive index of 1.520-1.510 within a temperature range of 10 to 60° C., and low temperature dependence.
[0030] The invention also relates to the application of the styrene-acrylonitrile-acrylate terpolymer transparent resin in the preparation of transparent ABS resin.
[0031] The transparent copolymer resin can be blended with acrylonitrile-butadiene-styrene resin to prepare transparent ABS resin, and the transparent ABS resin composition comprises 50-85% of the transparent copolymer resin and 15-50% of ABS resin, and other conventional additives can also be added. In addition to the above-mentioned good physical properties, the refractive index of the transparent ABS has a low temperature dependence.
[0032] The beneficial effects of the present invention are:
[0033] The temperature dependence of the phase refractive index of the transparent resin prepared by the present invention is low, thereby reducing the defect that the optical performance of the transparent ABS resin deteriorates with temperature changes. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1It is a schematic diagram of the reaction mode of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0036] The copolymer related structure and performance test methods are as follows:
[0037] Glass transition temperature (Tg): tested by Swiss METTLER instrument, unit: °C;
[0038] Relative molecular weight (Mw) and molecular weight distribution (PDI): tested by Shimadzu 20AD instrument, relative molecular weight unit is g / mol;
[0039] Residual monomer (GC): tested by Agilent 7890B instrument, unit: ppm;
[0040] Color (b value): The yellowness index of the sample was measured using a Hunter Lab colorimeter;
[0041] Melt index (MFR): tested using CEAST MF30 melt index meter, unit: g / 10min;
[0042] Refractive Index (RI): Measured according to ASTM standard D 542 on 2 mm injection molded plaques.
[0043] Haze value (H): The haze value of a 2 mm injection-molded sheet was measured according to ASTM D1003.
[0044] Linear relationship y=a1x+b1: Test the refractive index of 2 mm injection molded sheet sample at 10℃ / 20℃ / 30℃ / 40℃ / 50℃ / 60℃, plot with temperature as the horizontal axis, and obtain a1 and b1 by linear fitting.
[0045] The main raw material information is shown in Table 1:
[0046] Table 1. Main raw material information
[0047] Transparent ABS preparation:
[0048] 0.2 parts by weight of EBS, 0.1 parts by weight of 1076, 0.2 parts by weight of 618, and 0.2 parts by weight of magnesium stearate were added to a mixture of 15 parts by weight of HR181 and 85 parts by weight of the transparent copolymer resin of the embodiment / comparative example and blended. A twin-screw extruder was used to prepare the particle resin at 220°C, and an injection molding machine was used to injection mold an optical sheet at 220°C, and the physical properties of the transparent ABS were tested.
[0049] [Example 1]
[0050] The transparent copolymer resin was prepared as follows:
[0051] A free radical bulk polymerization method is adopted, 1000g toluene, 3500g methyl methacrylate, 1000g styrene, 500g acrylonitrile, 4.8g n-octyl mercaptan and 1.2g 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane are mixed in a reactor 1) with a gas phase circulating liquid, the reactor is heated to 140°C for reaction, when the toluene ratio in the gas phase circulating liquid is 15-20wt% and the temperature is 30-40°C, the polymerization mixture is transferred to a reactor 2), 0.24g diisopropylbenzene peroxide is added, and the reaction is continued at 150°C, when the toluene ratio in the gas phase circulating liquid is 35-45wt% and the temperature is 20-30°C, the polymerization mixture is transferred to a devolatilization tank, the devolatilization tank is heated to 220°C, and gradually evacuated to a vacuum degree of -0.1MPa, maintained for 15min, and after removing unpolymerized monomers, a transparent copolymer resin is obtained. The product analysis and copolymer performance test results, as well as the properties of the prepared transparent ABS are shown in Table 1.
[0052] Embodiment 2-6
[0053] A transparent copolymer resin was prepared according to the process substantially the same as that in Example 1. The process changes, product analysis and copolymer performance test results, and the properties of the prepared transparent ABS are shown in Table 1.
[0054] [Comparative Example 1]
[0055] A transparent copolymer resin was prepared according to the same process as in Example 1. A free radical bulk polymerization method was used. 1000 g of toluene, 3500 g of methyl methacrylate, 1000 g of styrene, 500 g of acrylonitrile, 4.8 g of n-octyl mercaptan and 1.2 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane were mixed in a reactor 1) with a gas phase circulating liquid. The reactor was heated to 140° C. for reaction. When the toluene ratio in the gas phase circulating liquid was 15-20 wt % and the temperature was 30-40° C., the polymerization mixture was transferred to a reactor 2) and 0.24 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, continue to react at 150°C, when the toluene ratio in the gas phase circulating liquid is 35-45wt% and the temperature is 20-30°C, transfer the polymerization mixture to the devolatilization tank, heat the devolatilization tank to 220°C, and gradually evacuate to a vacuum degree of -0.1MPa, maintain for 15 minutes, remove the unpolymerized monomers, and obtain a transparent copolymer resin. The product analysis and copolymer performance test results, and the prepared transparent ABS properties are shown in Table 1.
[0056] [Comparative Example 2]
[0057] A transparent copolymer resin was prepared according to a process substantially the same as that in Example 1. A transparent copolymer resin was prepared according to a process substantially the same as that in Example 1. A free radical bulk polymerization method was used. 1000 g of toluene, 3500 g of methyl methacrylate, 1000 g of styrene, 500 g of acrylonitrile, 4.8 g of n-octyl mercaptan and 1.2 g of diisopropylbenzene peroxide were mixed in a reactor 1) with a gas phase circulating liquid. The reactor was heated to 140° C. for reaction. When the proportion of toluene in the gas phase circulating liquid was 15-20 wt %, the temperature was 30-40° C., the polymerization mixture was transferred to a reactor 2), 0.24 g of diisopropylbenzene peroxide was added, and the reaction was continued at 150° C. When the proportion of toluene in the gas phase circulating liquid was 35-45 wt % and the temperature was 20-30° C., the polymerization mixture was transferred to a devolatilization tank. The devolatilization tank was heated to 220° C. and gradually evacuated to a vacuum degree of -0.1 MPa, which was maintained for 15 min. After removing the unpolymerized monomers, a transparent copolymer resin was obtained. The product analysis and copolymer performance test results, as well as the properties of the prepared transparent ABS are shown in Table 1.
[0058] [Comparative Example 3]
[0059] A transparent copolymer resin was prepared according to the same process as in Example 1 by free radical bulk polymerization. 1000 g of toluene, 3500 g of methyl methacrylate, 1000 g of styrene, 500 g of acrylonitrile, 4.8 g of n-octyl mercaptan and 1.2 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, the reactor is heated to 140°C for reaction, when the proportion of toluene in the gas phase circulating liquid is 15-20wt% and the temperature is 30-40°C, the polymerization mixture is transferred to the reactor 2), 0.24g of diisopropylbenzene peroxide is added, and the reaction is continued at 140°C, when the proportion of toluene in the gas phase circulating liquid is 35-45wt% and the temperature is 20-30°C, the polymerization mixture is transferred to the devolatilization tank, the devolatilization tank is heated to 220°C, and gradually evacuated to a vacuum degree of -0.1MPa, maintained for 15min, and after removing the unpolymerized monomer, a transparent copolymer resin is obtained. The product analysis and copolymer performance test results, and the prepared transparent ABS properties are shown in Table 1.
[0060] According to the test results in Table 1, the transparent copolymer resin prepared in Examples 1-6 of the present invention has higher fluidity, lower monomer residue and whiter color; meanwhile, within the range of 10-60°C, the temperature dependence of the refractive index is lower.
[0061] Table 1. Reaction conditions and product test results of Examples 1 to 6 and Comparative Examples 1 to 3
[0062]
[0063] Table 1 (continued)
[0064]
[0065]
Claims
1. A styrene-acrylonitrile-acrylate terpolymer transparent resin, wherein the relationship between the refractive index y and the temperature x (°C) of the terpolymer transparent resin satisfies the linear relationship of y=a1x+b1 within the temperature range of 10-60°C, and a1 is between -0.03% and -0.01%, b1 is between 1.5 and 1.6, and has a refractive index of 1.520-1.
510.
2. A method for preparing the transparent resin as claimed in claim 1, comprising: a) mixing an aromatic vinyl monomer, an alkyl (meth)acrylate monomer, an unsaturated nitrile monomer, an organic peroxide initiator A, a chain transfer agent and a reaction medium to obtain a reaction mixture; b) adding the reaction mixture described in a) into the reactor 1) to carry out a bulk polymerization reaction, wherein the reaction temperature of the reactor 1) is regulated by a gas phase circulating liquid, wherein the temperature of the gas phase circulating liquid is 30 to 40° C., and the proportion of the reaction medium in the circulating liquid is 15 to 25%, to obtain a polymerization mixture; c) adding the polymerization mixture described in b) and an organic peroxide initiator B into the reactor 2) to carry out a bulk polymerization reaction, wherein the temperature of the gas phase circulating liquid in the reactor 2) is 20 to 30° C. and the proportion of the reaction medium in the circulating liquid is 35 to 45%, to obtain a polymerization mixture; d) After step c), the polymerization mixture is transferred to a devolatilizer to remove light components to obtain a transparent copolymer resin.
3. The method according to claim 2, wherein: The amounts of the components in step a) are: 50 to 70 parts by weight of an alkyl (meth)acrylate monomer, 10 to 30 parts by weight of an aromatic vinyl monomer, 5 to 20 parts by weight of an unsaturated nitrile monomer and 10 to 20 parts by weight of a reaction medium; Preferably, in step a), based on 100 parts by weight of the aromatic vinyl monomer, (meth) alkyl acrylate monomer, unsaturated nitrile monomer and reaction medium mixture described in a) (referred to as "initial raw materials and reaction medium mixture"), the amount of organic peroxide initiator A added is 0.01 to 0.03 parts by weight, and the amount of chain transfer agent added is 0.05 to 0.2 parts by weight.
4. The method according to claim 2 or 3, wherein: The (meth) alkyl acrylate monomer includes one or more of methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, and butyl acrylate. More preferably, the (meth) alkyl acrylate is methyl methacrylate; and / or The aromatic vinyl monomer includes at least one of styrene and α-methylstyrene, and more preferably, the aromatic vinyl monomer is styrene; and / or The unsaturated nitrile monomer includes at least one of acrylonitrile and methacrylonitrile, and more preferably, the unsaturated nitrile monomer is acrylonitrile; and / or The reaction medium is one or more of cyclohexane, toluene, xylene, and ethylbenzene, preferably toluene; and / or Initiator A is at least one of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane and 1,1-bis(tert-butylperoxy)cyclohexane; and / or The chain transfer agent is a mercaptan-based compound, including at least one of tert-dodecyl mercaptan and n-octyl mercaptan. More preferably, the chain transfer agent is n-octyl mercaptan.
5. The method according to claim 2 or 3, wherein: The reaction temperature of step b) is 130-145° C., and the bulk polymerization conversion rate is 50-55%.
6. The method according to claim 2 or 3, wherein: The reaction temperature of step c) is 145-155° C., and the bulk polymerization conversion rate is 75-80%.
7. The method according to any one of claims 2 to 6, wherein: In step c), the amount of organic peroxide initiator B added is 0.002 to 0.005 parts by weight based on 100 parts by weight of the mixture of the initial raw materials and the reaction medium; Preferably, initiator B is one or more of cumene peroxide and dicumyl peroxide, more preferably dicumyl peroxide.
8. The method according to any one of claims 2 to 7, wherein: In step d), the devolatilization temperature is 210-240° C., the absolute pressure is 3-10 kPaa, and the devolatilization time is 10-15 min.
9. Use of the transparent resin according to claim 1 in preparing transparent ABS resin.
10. A transparent ABS resin, comprising a styrene-acrylonitrile-acrylate terpolymer transparent resin (preferably with a content of 50-85%), wherein the relationship between the refractive index y and the temperature x (°C) of the terpolymer transparent resin satisfies the linear relationship y=a1x+b1 within a temperature range of 10-60°C, and a1 is between -0.03% and -0.01%, b1 is between 1.5 and 1.6, and has a refractive index of 1.520-1.510.
Citation Information
Patent Citations
Process for preparing thermoplastic transparent resin
CN1372579A
Method of preparing transparent copolymer resin, transparent copolymer resin prepared by the method, and resin blend composition including the transparent copolymer resin
CN101072803A
Method of preparing transparent ABS resin by adopting continuous body device
CN106699981A
Transparent copolymer resin as well as preparation method and application thereof
CN117186296A
Cited By
ABS (Acrylonitrile Butadiene Styrene) rubber powder, low-haze transparent ABS resin and preparation method thereof
CN121203083A